A multiphase MPS method coupling fluid–solid interaction/phase-change models with application to debris remelting in reactor lower plenum. (February 2022) - Duan, Guangtao; Yamaji, Akifumi; Sakai, Mikio
Highlights: The fluid–solid and solid–solid interaction models are coupled into an improved MPS method. A new speedup algorithm is proposed for the multi-time-scale issue in debris remelting. Numerical examples demonstrated capability of the coupled models and the speedup algorithm. The influence of debris size and decay power on local hot spots was discussed. Abstract: In a postulated severe accident, the in-vessel debris remelting may result in severe local hot spots, probably threatening the reactor pressure vessel (RPV). The moving particle semi-implicit (MPS) method has great potential for simulating such complicated phenomena. To simulate debris remelting, the models for fluid–solid interactions and solid–solid collisions are coupled into an improved MPS method. A new speedup algorithm that can consider the flow and heat-transfer simulations separately is proposed to handle the multi-time-scale problem in debris remelting. The influence of debris size and decay heat power on the occurrence of local hot spots and RPV breach patterns during debris melting was investigated. It is found that (1) large debris blocks tended to result in severe local hot spots probably causing a lower breach point and (2) high decay power might cause the migration of local hot spots probably producing limited ablation to the vicinity of the RPV wall.